DAMPAK VARIABEL MAKROEKONOMI TERHADAP TINGKAT PENGANGGURAN TERBUKA PROVINSI BALI - Made Santana Putra Adiyadnya; Gde Bagus Brahma Putra; I Gusti Ayu Asri Pramesti (Jurnal AKSES, 2019)
Economic development is a process increase in real income of the population in a country as sustainably. Macro economy growth become one of the indicators for rate economic conditions a country. Unemployment in macro economy is a complicated problem from human resources in each country, including Indonesia. Bali province is one of province has a very tight population, so there are many workers and unemployment. The purpose of this study are to know the effect of economy growth, inflation and investation partially to open unemployment rate of Bali Province and to know the effect of economy growth, inflation and investation simultaneously to open unemployment rate of Bali Province.The result of this research are economy growth variable partially has a negative and significant effect to open unemployment rate of Bali Province, while inflation variable partially has an insignificant effect to open unemployment rate of Bali Province, and investation variable partially has a positive and significant effect to open unemployment rate of Bali Province. The last one, that economy growth, inflation and investation simultaneously has a significant effect to open unemployment rate of Bali Province.